Impact of Non-Farm Activities on Income: A Case of Rural Areas of District Bahawalpur - Kazmi, Syed Mumtaz Ali; Imran, Syed Muhammad; Nasim, Ismat; Ayub, Muahammad (iRASD Journal of Economics, 2023)
Over 68% of Pakistan's population lives in rural areas, and they primarily rely on agriculture to make a living. Pakistan's rural non-farm economy is diverse, encompassing a wide range of activities. The objective of the current study is to quantify the effect of rural non-farm activities on rural household's income in Punjab, Pakistan's district of Bahawalpur. For households with lower incomes, the non-farm market is one of their main sources of income. The study's respondents were chosen using a multistage sampling process. A standardized questionnaire was used to collect data throughout five stages. The findings demonstrate that non-farm activities increase the rural household's income and employment. The income of the household is positively and significantly influenced by education and experience. The results also shows that non-farm activities as well as non-farm participants augments rural income. From the policy prospective, it is recommended that in rural areas non-farm activities should be promoted.